Răspuns :
15+y:4=z
(3xz+27):9-5=4
3xz+27=a
a:9-5=4
a:9=b; b-5=9
a:9=9
a=81
3xz+27=81
3xz=81-27
3xz=54
z=54:3
z=18
15+y:4=18
y:4=18-15
y:4=3
y=12
7+x=12
x=12-7
x=5
verif: {3x[15+(7+5):4]+27}:9-5=4
(3xz+27):9-5=4
3xz+27=a
a:9-5=4
a:9=b; b-5=9
a:9=9
a=81
3xz+27=81
3xz=81-27
3xz=54
z=54:3
z=18
15+y:4=18
y:4=18-15
y:4=3
y=12
7+x=12
x=12-7
x=5
verif: {3x[15+(7+5):4]+27}:9-5=4
{3 * [15 + (7 + x) : 4] + 27} : 9 = 4 + 5
3 * [15 + (7 + x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
7 + x = 3 * 4
x = 12 - 7
x = 5
3 * [15 + (7 + x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
7 + x = 3 * 4
x = 12 - 7
x = 5